Effect of Mixed Li+/Na+-ion Electrolyte on Electrochemical Performance of Na4Fe3(PO4)2P2O7 in Hybrid Batteries - Nina V. Kosova (Batteries, 2019)
The mixed sodium-iron ortho-pyrophosphate Na4Fe3(PO4)2P2O7 (NFPP) is a promising Na-containing cathode material with the highest operating voltage among sodium framework structured materials. It operates both in Na and Li electrochemical cells. When cycled in a hybrid Li/Na cell, a competitive co-intercalation of the Li+ and Na+ ions occurs at the cathode side. The present study shows that this process can be tuned by changing the concentration of the Na+ ions in the mixed Li+/Na+-ion electrolyte and current density. It is shown that if the Na concentration in the electrolyte increases, the specific capacity of NFPP also increases and its high-rate capability is significantly improved.